A molecular dynamics study employing bimetallic Co-CuHAB nanosheets for seawater desalination - Hong, Terence Zhi Xiang (2023)
Bimetallic MOFs, which contain two different types of metal nodes within their porous structures, have emerged as a novel class of materials that exhibit tunable properties, rendering them suitable for various applications. In this research, molecular dynamics (MD) simulations are conducted to assess the performance of 2D Hexaaminobenzene (HAB)-derived MOF membranes in reverse osmosis seawater desalination. The membranes display different Co:Cu metal node ratios and degrees of offset nanosheets, and their ion rejection rates and water flux values are compared. In particular, their behaviors are explained through the corresponding radial distribution functions, density distributions, and interaction energy values. Our findings reveal that of the four MOF membranes studied, CuHAB exhibits the best performance in terms of water flux. In addition, the pore diameter of the MOFs is dependent on the ratio of the Co and Cu nodes inside their respective MOF membranes. To achieve high water flux, it is recommended for the membranes to have large hydrophobic pores, while the membrane must display poor salt adsorption to prevent salt ions from permeating through. It is also observed that Co nodes exhibit greater affinity toward the O atoms of the water molecules and the Cl- ions than the Cu nodes. Due to the hydrophobic nature of the small CoHAB pores, offsetting the nanosheets that constitute the membranes can improve salt rejection but show no significant effect on water flux. Overall, this study shows that MD simulations can effectively determine the optimal ratio of metal nodes in bimetallic 2D MOF membranes to achieve desirable water flux values and ensure excellent salt rejection.